Breaking Down: On Publicity as Capacity. Issue 3 (26th May 2020) - Johnson, Jenell
ABSTRACT: This essay argues for understanding publicity as a kind of ability. Using a brief reading of accounts of nervous breakdown in US newspapers, it suggests that the condition was characterized by the inability, usually temporary, to appear in public. Previous scholarly approaches to public access have focused on the question of who is let in and who is kept out; this essay suggests that the capacity for public appearance also enables—and constrains—rhetorical action. In conclusion, it suggests that the public may be thought of as a kind of kairotic space, which allows us to see how publics may be disabling, but also how dispublicity might be accommodated.